Plan de marketing para el Restaurant Las Delicias de Orlanda en el centro de la ciudad de Quevedo, año 2014 - Cabrera Vera, Orlanda Manuela (2013)
This research aims to investigate this situation and through an investigation of market to determine the demand for food in order to propose a marketing plan to publicize the restaurant led to a market segment that looking to eat healthy. It is therefore justified the conduct of this study in the importance and the need to offer consumers a regime of different food consumption, where to improve and meet their needs. Today, it is consuming a lot fast food, so many times the parents work and the most practical purchase what is the step, in our city there are many local fast food that is not beneficial for the health because of a poor diet are the diseases and the most common is the obesity of the people. That is why people have arrived in a state of analysis of your current power already that there is a great concern to change their eating habits, there are usually some factors such as: medical recommendations, targets for reducing weight, search for a better alternative to take care of your health. The restaurant The delights of Orlanda has an alternative of consumption of food prepared by their professional Chef, but it is not known due to the lack of targeted advertising in its target market of the city of Quevedo, and this is causing a low growth and loss of the sales opportunity, clearing the problem of how a marketing plan for the restaurant the delights of Orlanda affects the level of sales of their prepared food in the city of Quevedo. The main objective of the work was: to develop the Marketing Plan for the restaurant the delights of Orlanda from the city of Quevedo, 2014.